RELATIONSHIP MANAGEMENT AND TRANSPOSABLE IDENTITY OF TEACHERS IN THE DISTRICT OF MAAYON - Fabillon, Mary Grace D. (President University, 2024)
The study investigated the level of relationship management and degree of transposableidentity of teachers in the District of Maayon. The respondents of the study were 219 randomlyselected elementary school teachers in the District of Maayon. The study used the descriptivecorrelational research design. Data were collected using a validated and reliability-testedresearcher-made questionnaire. Statistical tools used to analyze and interpret data werefrequency count, percentage, mean, t-test, and analysis of variance, and Pearson r. The resultsrevealed that the level of relationship management and the degree of transposable identity ofteachers were very effective. There was no significant difference in the relationshipmanagement of teachers when they were grouped according to sex, age, educationalattainment, and estimated monthly income. There was significant difference the degree oftransposable identity of when they were grouped according to sex, while there was nosignificant difference when grouped according age, educational attainment, and estimatedmonthly income. The relationship management of teachers was found to be significantlyassociated with transposable identity